PERAMALAN CURAH HUJAN MENGGUNAKAN METODE ANALISIS SPEKTRAL - WAHYUNI, NI PUTU MIRAH SRI; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 5 No 4 (2016), 2016)
The purpose of this research is the model of forecasting rainfall using spectral analysis method. To obtain complete information on characteristics of time series data we need to examine periodicity of the data. Examining the periodicity of time series data in the frequency domain is called spectral analysis. The results of spectral analysis show that periodogram is clearly dominated by a very large peak at frequency . This frequency corresponds to period of 12 cycle per month. Based on the results of analysis of time series data rainfall is SARIMA (0,1,1)(0,1,1) 12 where the model can be written as The result indicates minimum rainfall happen in January and maximum rainfall happen in August.
Keywords: Forecasting; Periodicity; SARIMA; Spectral Analysis